The impact of globalization on traditional culture and values of modern Arab society (Journal of Oriental Studies, 2024)
The article deals with the problems of the changes in traditional cultureand values of modern Arab society in the process of globalization, particularlyin religion, language, etiquette, clothing and food. Current globalchanges in the world and a new period of mankind have an impact onthe development of the states in the world including Arab countries. Globalizationis reflected in economic development, social status, education,culture, moral and religious spheres of Arab countries.
Keywords: the process of globalization; the impact of globalization; Arab society; religion; the Arabic language; Arab etiquette; Arab national clothes; Arab national food